Microsurgical sequestectomy at 36 weeks of pregnancy: A case report - J. Kummer; J. Maier; D. Moskopp; L. Hellmeyer (Elsevier, 2018)
About 30% of pregnant women experience lower back pain. The cause is usually increased mechanical stress combined with the ligament laxity induced by relaxin. Rarely, lower back pain is related to disc herniation. We report such a case, where microsurgical sequestectomy was performed at 36 weeks and three days of gestation because of severe extensor paresis of the left foot and big toe. The case shows that microsurgical treatment during pregnancy is safe. After treatment the patient regained full motor function and her pain regressed. She had a spontaneous vaginal delivery at 38 weeks. Keywords: Pregnancy, Lumbar disc prolapse, Microsurgical sequestectomy